Computational fluid dynamics modeling of floating treatment wetland retrofitted stormwater pond: Investigation on design configurations - Nuruzzaman, Md; Anwar, Faisal; Sarukkalige, Pryantha Ranjan (Elsevier, 2023)
Floating Treatment Wetland (FTW) is a cost-effective and easy-to-retrofit device for stormwater treatment. Its treatment efficiency largely depends on the fraction of inflow entering FTW and the residence time within it. Thus hydrodynamics play a crucial role, which is affected by the design configurations of FTW and stormwater pond. Despite a spike in research on FTWs, very little is known about how various design configurations affect treatment efficiency by an FTW. Our study hypothesizes that relative positions of FTW geometry, FTW position and pond inlet–outlet have impact on the hydrodynamics and as a consequence, treatment efficiency. To explore these design features, we employed computational fluid dynamics (CFD) modeling conducted in ANSYS Fluent, validated by experimental data to examine the impact of the aforementioned design features. The results revealed that circular FTW geometry positioned near inlet coupled with center inlet–side outlet configuration achieved the highest removal (94.8%) for a non-dimensional removal rate of krtHRT = 20 (kr is the first order removal rate in per day, tHRT is the nominal hydraulic residence time of the pond in days). Far side inlet–side outlet configuration performed the worst due to profound promotion of short-circuiting. FTW positioned near inlet performed better (61.8% mass removal on an average) than center (42.7%) and near outlet positions (54.1%) for krtHRT = 20. Sensitivity analysis revealed that the treatment efficiency is most sensitive to inlet–outlet configurations. The design implications of this study will help practitioners achieving better water quality and ecological improvement goals.